Accelerating degraded land rehabilitation through liquid soil conditioning - Marjenah, Marjenah; Kiswanto, Kiswanto; Karyati, Karyati; Rosamah, Enih; Sarminah, Sri; Riyayatsyah, Riyayatsyah (Brawijaya University, 2026)
Mining activities led to land degradation, which in turn resulted in food insecurity. Additionally, it limited post-mine plant growth actions but did not initiate any new actions. The drawings describe the involvement of soils resulting from various land uses following degradation actions, including agriculture, forestry, and other land uses. It gives an overall description of the activities and processes. The primary factors involved in land degradation include structural changes in soil, pH, and the activity of various components. The Liquid Soil Conditioning (LSC) solution developed in the study provides a resource that can be used as an application option for land restoration. This study evaluated the post-coal mining problem in West Samboja, East Kalimantan Province, Indonesia. It offers a prospect to understand soil conditions related to the availability of essential nutrients and microorganisms. This study examined various physical, chemical, and?biological characteristics of the soil. The results showed that LSC can make land management more sustainable. The LSC can mitigate the opposing effects on soil and support beneficial?soil microbes. This innovation not only restores damaged land and makes it more suitable for planting, but also increases land production and supports the other functions of the natural ecosystem. Those working in land restoration should conceivably use LSC more?frequently. This method can?support more sustainable post-mining land management when accompanied by regular soil monitoring and further research in advance.